Emergencies in pediatric oncology - Boyce, Allison E.; Scheinemann, Katrin (Springer New York, 2012)
Pediatric oncology is a considerably complex discipline requiring frequent need for reference material.  Emergencies in Pediatric Oncology meets this objective by serving as a concise, practical resource for the hurried physician. Replete with diagrams and written in a clear, succinct style, this title offers an easy-to-read guide especially useful for residents, fellows, and nurses. Providing an overview of the epidemiology of childhood cancer and the history of its treatment, this title also addresses a range of key problems in the pediatric oncologic setting, covering the most common emergencies and providing short, practical guidelines on how to handle them. Written by authorities from an array of disciplines, this helpful resource provides answers and concrete guidance and is a valuable contribution to the literature in pediatric oncology.